An Analytical Study of Adaptive Reuse in Jeddah's Historic Buildings: Beit Jokhdar as a Model - Albaghajati, زينة محمد; ربا زكريا شاهين (Journal of King Abdulaziz University: Environmental Design Sciences, 2026)
This research aims to study the adaptive reuse of Beit Jokhdar as a model for the restoration of historical houses, their rehabilitation, and transformation into heritage hotels (boutique hotels) or any other activity that combines sustainability while preserving their historical identity. The preservation and investment in the region's urban heritage is one of the objectives of Saudi Vision 2030, and the Ministry of Culture and its relevant authorities are making diligent efforts to revitalize the Historic Jeddah area in accordance with international standards such as UNESCO and ICOMOS. The research employed a descriptive analytical methodology of Beit Jokhdar within the context of Historic Jeddah. Primary data was based on a field visit to the hotel, utilizing field observation and photographic documentation tools to analyze the architectural features that have been preserved. Additionally, a semi-structured interview was conducted with the hotel's operations management. The findings revealed that what distinguishes the revitalization of Beit Jokhdar and its conversion into a heritage hotel is the suitability of its functional spaces for use as a boutique hotel, which supports its architectural, economic, and social sustainability. From the architectural aspect, the house was restored to preserve its heritage and original splendor using traditional building materials and methods. The interior design selections were strategically implemented to complement the property's primary function as a hospitality venue, showcasing regional heritage elements through a contemporary lens, which significantly elevates the overall guest experience. In terms of economic sustainability, Beit Jokhdar has helped attract tourists from around the world as a heritage hotel and hospitality venue, resulting in social and economic impacts in the Historic Jeddah area. The research recommends studying and documenting leading practices in the restoration and repurposing of heritage buildings in Historic Jeddah and disseminating the culture and expertise of practitioners and researchers.